Draft Annual Plan for Assam 1980-81 Volume : I Introduction and Summary Statements - Planning Commission (Planning Commission, 1980)
This draft envisages a total outlay of Rs. 18729.87 lakhs during 1980-81, made up of Rs. 17459.72 lakhs in the General Areas and Rs. 1270.15 Lakhs in the Hill Areas of the State. The Hill Plan will be supplemented by a proposed Additive Central Assistance of Rs. 643.50 lakhs, thereby making the total size of the Hill Plan Rs. 1913.65 lakhs. Similarly, it is anticipated that Special Central Assistance of Rs. 336.00 lakhs would be available for supplementing the Tribal Sub Plan in the General Areas, during 1980-81.
Government of Assam, Planning and Development Department
Government of Assam, Planning and Development Department